2010
DOI: 10.1519/jsc.0b013e3181a392b2
|View full text |Cite
|
Sign up to set email alerts
|

Sodium Bicarbonate Ingestion and Boxing Performance

Abstract: Boxing is a sport that consists of multiple high-intensity bouts separated by minimal recovery time and may benefit from a pre-exercise alkalotic state. The purpose of this study was to observe the ergogenic potential of sodium bicarbonate (NaHCO3) ingestion on boxing performance. Ten amateur boxers volunteered to participate in 2 competitive sparring bouts. The boxers were prematched for weight and boxing ability and consumed either 0.3 g.kg(-1) body weight (BW) of NaHCO3 (BICARB) or 0.045 g.kg(-1) BW of NaCl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

13
66
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(82 citation statements)
references
References 23 publications
13
66
0
3
Order By: Relevance
“…There are various studies showing the beneficial effects of both acute and chronic SB ingestion on high-intensity exercise capacity (McNaughton et al 2008) and on performance in various sports, such as judo (Artioli et al 2007), swimming (Lindh et al 2008), and boxing (Siegler and Hirscher 2010). Several qualitative reviews are available on the effects of BA on exercise performance and capacity (Artioli et al 2010;Derave et al 2010;Sale et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are various studies showing the beneficial effects of both acute and chronic SB ingestion on high-intensity exercise capacity (McNaughton et al 2008) and on performance in various sports, such as judo (Artioli et al 2007), swimming (Lindh et al 2008), and boxing (Siegler and Hirscher 2010). Several qualitative reviews are available on the effects of BA on exercise performance and capacity (Artioli et al 2010;Derave et al 2010;Sale et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have examined the ergogenic potential of SB on short-distance swimming performance (i.e., 100 and 200 m or 100 and 200 yards) and interval swimming performance (Gao et al 1988;Pierce et al 1992;Lindh et al 2008;Pruscino et al 2008;Siegler and Hirscher 2010;Joyce et al 2012). However, results are quite conflicting; some studies reported no effect of SB on timetrial performance (Pierce et al 1992;Pruscino et al 2008;Joyce et al 2012), one reported a positive effect on swimming trials (Lindh et al 2008), and others reported improved interval swimming performance (Gao et al 1988;Siegler and Hirscher 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The researchers observed a non-significant 2% improvement in work performed and no significant differences in post exercise pH values. In contrast, Siegler and Hirsher 27 reported a significant improvement in boxing performance without observing significant differences between conditions in post exercise pH. Most researchers who have reported significant differences in performance, however, also observed significant differences in post exercise pH values.…”
Section: Discussionmentioning
confidence: 89%
“…The difference in pH values in the treatment group between pre-ingestion and 1 hr post-ingestion (0.032) is similar to the differences in pH values reported by other researchers investigating the effects of induced metabolic alkalosis via NaHCO3 ingestion. [25][26][27] Additionally, all except one subject had a post ingestion pH of greater than 7.42, indicating that NaHCO3 ingestion did induce metabolic alkalosis and presumably enhanced extracellular buffering capacity.…”
Section: Discussionmentioning
confidence: 95%